Morphology and Electric Conductance Change Induced by Voltage Pulse Excitation in (GeTe)2/Sb2Te3 Superlattices - Bolotov, Leonid; Saito, Yuta; Tada, Tetsuya; Tominaga, Junji (Scientific reports, 2016)
Chalcogenide superlattice (SL) phase-change memory materials are leading candidates for non-volatile, energy-efficient electric memory where the electric conductance switching is caused by the atom repositioning in the constituent layers. Here, we study the time evolution of the electric conductance in [(GeTe) 2 /(Sb 2 Te 3 ) 1 ] 4 SLs upon the application of an external pulsed electric field by analysing the structural and electrical responses of the SL films with scanning probe microscopy (SPM) and scanning probe lithography (SPL). At a low pulse voltage (1.6–2.3 V), a conductance switching delay of a few seconds was observed in some SL areas, where the switch to the high conductance state (HCS) is accompanied with an SL expansion under the strong electric field of the SPM probe. At a high pulse voltage (2.5–3.0 V), the HCS current was unstable and decayed in a few seconds; this is ascribed to the degradation of the HCS crystal phase under excessive heating. The reversible conductance change under a pulse voltage of opposite polarity emphasised the role of the electric field in the phase-transition mechanism.